MAKRODESIGN OF PERSPECTIVE MODEL OF THE INTEGRATED CLINICAL PRACTICE OF STUDENTS OF HIGHER EDUCATION INSTITUTION - M. A. Kartavykh; I. V. Prokhorova; E. L. Ageeva (Вестник Мининского университета, 2017)
In article application of a phenomenon of macrodesign in professional pedagogics is proved. The essence of macrodesign of perspective model of the integrated clinical practice of students in conceptual and outline types is opened. The concept (avant-project) it is presented at the scientific and methodological and didactic levels. The outline sketch creates idea of organizational and technological aspects of the integrated clinical practice of students.